2022
DOI: 10.3390/su14084708
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Political Connections on Corporate Green Innovation: The Mediating Effect of Corporate Social Responsibility and the Moderating Effect of Environmental Public Opinion

Abstract: The construction industry is the lifeblood of the national economy; thereby, to some extent, the green transformation of the construction industry is representative of the industrialization levels of modern construction, especially in China. Based on the panel data of A-share listed companies in China’s construction industry from 2014 to 2019, this work studies the influence mechanism of political connection on corporate green innovation by establishing a multiple regression model, analyzes the realization pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The stakeholders expect to improve the performance of firms, and the responsibility of any firm management is to work for it. Furthermore, any firm's stakeholders expect to improve the firm's performance for the achievement of social goals [39]. The reliability of firm performance and its sustainable advancement can provide a better working opportunity for business [40,41].…”
Section: Moderating Role Of Stakeholder Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stakeholders expect to improve the performance of firms, and the responsibility of any firm management is to work for it. Furthermore, any firm's stakeholders expect to improve the firm's performance for the achievement of social goals [39]. The reliability of firm performance and its sustainable advancement can provide a better working opportunity for business [40,41].…”
Section: Moderating Role Of Stakeholder Expectationsmentioning
confidence: 99%
“…Better employment opportunities for a company may be made possible by the consistency of firm performance and its advancement in operating. According to Wang, Peng [39], while each company undoubtedly has different objectives, all of them must live up to the expectations of its stakeholders. The management of any company must work in the stated direction of the stakeholders.…”
Section: Plos Onementioning
confidence: 99%
“…In order to verify the effect of the digitalization level of enterprises on the green innovation of enterprises, we reference to the test method of Wang et al (2022) [98], and a common panel data model ( 1) is constructed to test the effect of green innovation.…”
Section: Modelmentioning
confidence: 99%
“…Li and Shen [46] conducted empirical tests and concluded that cities with higher levels of happiness had higher levels of green innovation among the listed companies. Wang et al [47] found through their analysis of Chinese construction companies that the political affiliation of enterprises has a significant positive impact on green innovation. Zhang and Wang [48] found that corporate political ties have an inverted U-shaped relationship with green innovation.…”
Section: Enterprise Green Innovationmentioning
confidence: 99%